ANALISIS FAKTOR YANG MEMPENGARUHI TINGKAT KEMISKINAN PROVINSI DI PULAU JAWA - Liya nur Sari; Ida Nuraini (Jurnal Ilmu Ekonomi JIE, 2020)
Poverty is an issue that must be resolved by a country, especially developing countries. Poverty is also influenced by many factors such as income, health, education, unemployment and access to goods and services. The study research the effect of literacy rate, life expectancy, and an unemployment rate of poverty every province in Java Island in 2014-201. The research uses quantitative method. Data analysis using the panel data model by common effect, fixed effect and random effect. While for the best estimation model using chow test, Hausman test and LM test. The results of this study indicate that the best estimation model this study is a random effect model, which means literacy rate significantly negative effect on poverty, life expectancy significant positive effect on poverty, and unemployment rate significantly positive effect on poverty. Therefore, the government is expected to improve the quality of a strong planning strategy so that is can be achieved the purpose for the welfare of the poor, which is a form of success in developing a country.